2019
DOI: 10.1002/jcb.29193
|View full text |Cite
|
Sign up to set email alerts
|

Bif‐1/Endophilin B1/SH3GLB1 regulates bone homeostasis

Abstract: Skeletal tissue homeostasis is maintained via the balance of osteoclastic bone resorption and osteoblastic bone formation. Autophagy and apoptosis are essential for the maintenance of homeostasis and normal development in cells and tissues. We found that Bax‐interacting factor 1 (Bif‐1/Endophillin B1/SH3GLB1), involving in autophagy and apoptosis, was upregulated during osteoclastogenesis. Furthermore, mature osteoclasts expressed Bif‐1 in the cytosol, particularly the perinuclear regions and podosome, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Zhang et al found that S100A9 plays an essential pro-inflammatory role in sepsis-mediated acute liver injury by regulating AKT-AMPK-dependent mitochondrial energy metabolism [44]. SH3GLB1 is a Bax-binding protein, which is involved in autophagy and apoptosis [45]. SORT1 may affect the prognosis of sepsis and patient survival [46].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al found that S100A9 plays an essential pro-inflammatory role in sepsis-mediated acute liver injury by regulating AKT-AMPK-dependent mitochondrial energy metabolism [44]. SH3GLB1 is a Bax-binding protein, which is involved in autophagy and apoptosis [45]. SORT1 may affect the prognosis of sepsis and patient survival [46].…”
Section: Discussionmentioning
confidence: 99%
“…NLRC4 (NLR family CARD domain containing 4) was found to be up-regulated by MAPK pathway in pediatric sepsis, which also inhibited IL‑1β and IL‑18 production to contribute to the anti-inflammatory response [ 32 ]. SH3GLB1 was found as Bax binding protein at first, which is participated in autophagy and apoptosis [ 33 ]. PGS2 (phosphatidylglycerophosphate synthase 2) had a pro-inflammatory effect [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that Bif-1 is a negative regulator of RANKL-induced osteoclast generation. It may be a promising target for the treatment of RA and osteoarthritis ( 100 ). There are excessive T cells in synovium of RA patients.…”
Section: Diseasesmentioning
confidence: 99%